Non-Observance Politeness Maxim and Implicature on the TV Show Kids Say The Darndest Things - Salsabila, Talitha (Journal of Literature, Linguistics, & Cultural Studies, 2023)
The phenomenon of language development in the modern era is increasingly rapid through mass media, one of which is television shows. In addition to providing information, television also provides audiovisual entertainment to attract people to enjoy it. The non-observance maxim of politeness committed by public figures can be found. In this study, the author wants to examine how the non-observance politeness maxim and its implicature is in the video TV Show" Kids Say The Darndest Things" used by the host and children as the guest star. The method used by the author in this study is descriptive qualitative by combining two main theories. Firstly, to identify the type of politeness maxim most frequently unobserved by hosts and children, the author use Leech's theory (1983). Second, analyze the conversational implicature contained in utterances of hosts and children that unobserved maxim politeness with Grice's theory (1975). As a result, the writer found 37 non-observance of politeness maxims and conversational implicatures used by hosts and children as guest stars. The modesty maxim was the most common type used in this TV show, with 27%, followed by the approbation maxim, with 22%. Then, the same percentage of tact maxim and generosity maxim with 16%. Followed by a low rate of agreement maxim of 11% and a maxim of sympathy with 8%. The dominant conversation implicature on this TV Show is an implication that imply arrogance as a result of the non-observance of modesty maxim.The author suggests for further research that wants to examine the same topic to conduct research with different in indirect interaction